An acid‐doped ice membrane for selective proton transport. (23rd December 2020) - Sleutels, Tom; Kaniadakis, Iosif; Oladimeji, Olaniyi; van der Kooij, Harm; ter Heijne, Annemiek; Saakes, Michel
Summary: Cation exchange membranes need to have high permselectivity for protons to make these membranes suitable for, for example, energy storage devices. Here, we present the proof of concept for a proton selective membrane made of hydrochloric acid‐doped ice. The proton selectivity of this acid‐doped ice membrane is the result of defects in the ice structure, caused by the acid. Ice membranes were made from different hydrochloric acid concentrations (0.1‐2.0 M). The proton permselectivity of all ice membranes was above 99.7% when both Na + and K + were present. The resistivity decreased exponentially with the concentration of acid in the ice membrane, reaching a value of 12 Ω.cm. The ice membranes were tested in an electrochemical cell using the Fe/Fe 2+ and Fe 2+ /Fe 3+ redox couples, and a power density of 7 W/m 2 and OCV of 0.87 V were measured. The resistance of the ice membrane increased with time as protons moved from the ice structure, as determined from the higher pH of the ice after melting. These expelled protons (and corresponding counter charged ions) were not replaced by other mobile cations, indicating a permanent loss in conductivity, but not selectivity. To apply the ice membrane as a selective separator for protons in energy storage devices in the future, the membrane thickness should be reduced and the protons should be retained inside the ice. Abstract : A proton selective membrane was created by freezing acid. A high permselectivity over 99.7% was achieved for protons over Na + and K + . Although the ice membrane was thick (2 cm) a resistivity of 12 Ω.cm was achieved. A power density of 7 W/m 2 was reached.